Enterprise Systems: Curriculum design and assessment - Atif, Yacine; Al-Jaroodi, Jameela; Alkobaisi, Shayma; Jaffar, Ahmed; Ditsa, George; Campbell, Piers (Education and information technologies, 2011)
We present a curriculum that prepares students for supporting large Enterprise Information Systems (EIS). EIS is best explained through the evolution of Enterprise Resource Planning (ERP). These systems evolved over the last years driven by (1) changing business requirements and (2) new development capabilities provided by technologies evolution and software vendors’ innovation. These developments led to a new discipline—Enterprise Information Systems, which deals with issues whose focus is on creating and sustaining business benefits through the utilization of corporate IT infrastructure assets. Currently, EIS knowledge is essentially acquired on the job after substantial time of experience building and longer career ladder scale. This paper presents an experience of a curriculum implementation that prepares students for the pervasive EIS landscape in meeting today’s corporate needs. Our IT-based educational approach is evaluated as an alternative to prevailing Business-based approaches to EIS instruction. In this IT-rooted approach, the curriculum is divided into four sections: a Core IT block of courses followed by two progressive-levels of advanced EIS-related specialized subjects, and an industry-oriented field-training experience. Initially, a Core IT background provides a foundation for IT innovation in developing EIS components at sophomore-level. A junior-level of specialized instruction introduces integrated modules which form EIS platforms. Finally, supporting technologies of EIS-related processes and workflows are presented at senior-level of specialized EIS instruction. An assessment case study of the proposed Enterprise System programs is carried out through which we discuss the results of the curriculum performance.